Integrative functional genomic analysis of intron retention in human and mouse brain with Alzheimer's disease. Issue 6 (21st January 2021) - Li, Hong‐Dong; Funk, Cory C.; McFarland, Karen; Dammer, Eric B.; Allen, Mariet; Carrasquillo, Minerva M.; Levites, Yona; Chakrabarty, Paramita; Burgess, Jeremy D.; Wang, Xue; Dickson, Dennis; Seyfried, Nicholas T.; et al.
Abstract: Intron retention (IR) has been implicated in the pathogenesis of complex diseases such as cancers; its association with Alzheimer's disease (AD) remains unexplored. We performed genome‐wide analysis of IR through integrating genetic, transcriptomic, and proteomic data of AD subjects and mouse models from the Accelerating Medicines Partnership‐Alzheimer's Disease project. We identified 4535 and 4086 IR events in 2173 human and 1736 mouse genes, respectively. Quantitation of IR enabled the identification of differentially expressed genes that conventional exon‐level approaches did not reveal. There were significant correlations of intron expression within innate immune genes, like HMBOX1, with AD in humans. Peptides with a high probability of translation from intron‐retained mRNAs were identified using mass spectrometry. Further, we established AD‐specific intron expression Quantitative Trait Loci, and identified splicing‐related genes that may regulate IR. Our analysis provides a novel resource for the search for new AD biomarkers and pathological mechanisms.